Friedel–Crafts-type reaction of pyrene with diethyl 1-(isothiocyanato)alkylphosphonates. Efficient synthesis of highly fluorescent diethyl 1-(pyrene-1-carboxamido)alkylphosphonates and 1-(pyrene-1-carboxamido)methylphosphonic acid - Wrona-Piotrowicz, Anna; Zakrzewski, Janusz; Gajda, Anna; Gajda, Tadeusz; Makal, Anna; Brosseau, Arnaud; Métivier, Rémi (Beilstein Journal of Organic Chemistry, 2015)
Friedel–Crafts-type reaction of pyrene with diethyl 1-(isothiocyanato)alkylphosphonates promoted by trifluoromethanosulfonic acid afforded diethyl 1-(pyrene-1-carbothioamido)alkylphosphonates in 83–94% yield. These compounds were transformed, in 87–94% yield, into the corresponding diethyl 1-(pyrene-1-carboxamido)alkylphosphonates by treatment with Oxone®. 1-(Pyrene-1-carboxamido)methylphosphonic acid was obtained in a 87% yield by treating the corresponding diethyl phosphonate with Me3Si-Br in methanol. All of the synthesized amidophosphonates were emissive in solution and in the solid state. The presence of a phosphonato group brought about an approximately two-fold increase in solution fluorescence quantum yield in comparison with that of a model N-alkyl pyrene-1-carboxamide. This effect was tentatively explained by stiffening of the amidophosphonate lateral chain which was caused by the interaction (intramolecular hydrogen bond) of phosphonate and amide groups. The synthesized phosphonic acid was soluble in a biological aqueous buffer (PBS, 0.01 M, pH 7.35) and was strongly emissive under these conditions (λem = 383, 400 nm, τ = 18.7 ns, ΦF > 0.98). Solid-state emission of diethyl 1-(pyrene-1-carboxamido)methylphosphonate (λmax = 485 nm; ΦF = 0.25) was assigned to π–π aggregates, the presence of which was revealed by single-crystal X-ray diffraction analysis.
Keywords: amide; fluorescence; isothiocyanate; phosphonate; pyrene; thioamide; X-ray structure